A Vicious Cycle : How Pandemics Lead to Economic Despair and Social Unrest - Saadi Sedik, Tahsin (IMF Working Papers; Working Paper, 2020)
In this paper we analyze the dynamics among past major pandemics, economic growth, inequality, and social unrest. We provide evidence that past major pandemics, even though much smaller in scale than COVID-19, have led to a significant increase in social unrest by reducing output and increasing inequality. We also find that higher social unrest, in turn, is associated with lower ourput and higher inequality, pointing to a vicious cycle. Our results suggest that without policy measures, the COVID-19 pandemic will likely increase inequality, trigger social unrest, and lower future output in the years to come.